Metacercariae of Austrodiplostomum compactum (Trematoda, Diplostomidae) in non-native fish species in Brazil: a possible explanation for the high rate of parasitic infection - Ramos, Igor P.; Pagliarini, Cibele D.; Franceschini, Lidiane; Silva, Reinaldo J DA (FapUNIFESP (SciELO), 2020)
Metacercariae of Diplostomidae are widely distributed in America and may cause diplostomiasis, an ocular disease in fishes. The aim of this study is to report the occurrence of metacercariae of Austrodiplostomum compactum in Plagioscion squamosissimus (non-native fish species) from Nova Avanhandava Reservoir, Tietê River, Brazil and an explanation for the high infection rates with this parasite in the Paraná River Basin is proposed. Eyes of 70 hosts were examined, the metacercariae were preserved and identified. The prevalence (P), mean intensity of infection (MII) ± standard deviation, mean abundance (MA) ± standard deviation, were calculated and a bibliographic review was performed. There was no difference in parasitism between male and female hosts. The values of P = 80%, MII = 21.55 ± 3.25 and MA = 17.24 ± 2.91 were high, as in most studies in areas where P. squamosissimus were introduced, while these values were low in areas of natural occurrence. This may be explained by the genetic susceptibility of the host to the parasite. The entire population of P. squamosissimus from the Upper Paraná has been founded by a few specimens, resulting in very low genetic variability. Consequently, the population may be highly susceptible to A. compactum.